International Support for Educational Reform in Spain - Delgado, Lorenzo; Martín, Óscar J. (Historia y Memoria de la Educación, 2021)
In the 1960s, an international debate emerged on the role of education in the worldwide changes taking place in the political, social and economic sphere. Multilateral agencies such as the OECD and UNESCO played an important role in this process. Inspired by some of the central tenets of modernization and human capital theories, these organizations sought to steer the transitions from “traditional societies” to “modern” ones. In Franco’s Spain, this process of modernization was led by the technocratic sectors of the dictatorship, who aspired to become the agents of a project of change controlled from the state apparatus. International organizations actively participated in the analysis of the Spanish educational system, and recommendeding measures to bring it into line with the needs of economic development. The corollary of this work was their support for the 1970 General Education Law, which also enjoyed the endorsement of some of the main foreign allies of the Franco regime, such as the United States, the World Bank and the Ford Foundation. This support took the form of advice, funding, specialist training and educational assistance. The article addresses this whole process. It examines the efforts of various international actors and their involvement in the modernization of education in Spain as a step towards convergence with the Western model.